Preserving the inflated structure of lyophilized sporopollenin exine capsules with polyethylene glycol osmolyte - Corliss, Michael K. (2020)
Extracted from natural pollen grains, sporopollenin exine capsules (SECs) are robust, chemically inert biopolymer shells that posess highly uniform size and shape characteristics and that can be utilized as hollow microcapsules for drug delivery applications. However, it is challenging to extract fully functional SECs from many pollen species because pollen grains often collapse, causing the loss of architectural features, loading volume, and bulk uniformity. Herein, we demonstrate that polyethylene glycol (PEG) osmolyte solutions can help preserve the native architectural features of extracted SECs, yielding inflated microcapsules of high uniformity that persist even after subsequent lyophilization. Optimal conditions were first identified to extract SECs from cattail (Typhae angustfolia) pollen via phosphoric acid processing after which successful protein removal was confirmed by elemental (CHN), mass spectrometry (MALDI-TOF), and confocal laser canning microscopy (CLSM) analyses. The shape of SECs was then assessed by scanning electron microscopy (SEM) and dynamic image particle analysis (DIPA). While acid-processed SECs experienced high degrees of structural collapse, incubation in 2.5% or higher PEG solutions significantly improved preservation of spherical SEC shape by inducing inflation within the microcapsules. A theoretical model of PEG-induced osmotic pressure effects was used to interpret the experimental data, and the results show excellent agreement with the known mechanical properties of pollen exine walls. Taken together, these findings demonstrate that PEG osmolyte is a useful additive for preserving particle shape in lyophilized SEC formulations, opening the door to broadly applicable strategies for stabilizing the structure of hollow microcapsules.